Effect of variable relative permittivity on the thermodynamics of asymmetric valency aqueous salts - A. Quinones Rivera; Z. Abbas; C. Outhwaite; L. B. Bhuiyan (Condensed Matter Physics)
Experimentally determined empirical formulae for the concentration dependent relative permittivity of aqueous solutions of MgCl2 and NiCl2 are utilized to calculate the osmotic coefficient and the mean activity coefficient of these salts for a range of concentrations. The systems are modelled using the primitive model of electrolytes and analyzed using the symmetric Poisson-Boltzmann theory, the modified Poisson-Boltzmann theory, the mean spherical approximation, and the Monte Carlo simulations. Generally, the mean spherical approximation and the modified Poisson-Boltzmann theory reproduce the benchmark simulation data well up to ∼1.6 mol/dm3 or more in many instances, while the symmetric Poisson-Boltzmann results show discrepancies starting from ∼0.25 mol/dm3. Both the simulations and the theories tend to deviate from the corresponding experimental results beyond ∼1 mol/kg.